Evaluation of Phrae Model for Herbal Distribution from the Government Manufactories, Phrae Province - Nopsiri, Wimaluk (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
There are two herbal medicines government manufactories of WHO-GMP in Phrae province (Song and Den Chai Crown Prince Hospital). Phrae’s chief financial officer support the budget for herbal manufacture and distribution to government hospitals in Phare since 2014, namely Phrae model. Past operations, there are strengths, weaknesses, problems and barriers indicate to systematic management mechanism. Evaluation is an important mechanism to get information for improve and develop work efficiently in the future. So the researcher interested to study evaluation of Phrae model for herbal distribution from government manufactories to collect and analyze the data. The results of this research will be used as guideline for develop the operations of herbal distribution in Phrae, including herbal medicines management to effective, achieve the goal and leading to sustainability of Thai traditional and alternative medicine operations. This research is mixed methods research between qualitative and quantitative. Data were collected to two parts. Primary data, we select information providers by purposive sampling from role and participation, questionnaires were used as qualitative informations, and analyzed by using content analysis to explain characteristics and opinions of the sample groups. Secondary data were descriptive retrospective, study and collect informations from related documents, were analyzed by using descriptive statistics including: frequency, percentage, mean and standard deviation. The results of this study showed, Phrae model for herbal distribution from government manufactories were evaluated by the CIPP model that are high levels ( = 81.30, SD = 348.20). Four parts of the evaluation overall, the average are at a high levels. Performance results for the past 5 years (2018–2022), all Phrae outpatients who receive the services with the science of Thai traditional medicine were higher percentage rate level than Health Region 1 and Thai National level. Also percentage for Phrae’s herbal medicine prescription value was increased too.